2022
DOI: 10.1128/spectrum.01499-22
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Alteromonas Phage Lineage with a Broad Host Range and Small Burst Size

Abstract: The marine bacterium Alteromonas is prevalent in the global ocean with crucial ecological significance; however, little is known about the diversity and evolution of its bacteriophages that profoundly affect the bacterial communities. Our study characterized a novel genus of three newly isolated Alteromonas phages that exhibited a distinct infection strategy of broad host spectrum and small burst size.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 66 publications
0
10
0
Order By: Relevance
“…In this study, we reported the isolation and complete genome sequence of a filamentous phage designated ϕAFP1 from the South China Sea using the A. abrolhosensis strain JKT1 as the host bacterium. Until now, only 10 published reports about bacteriophages isolated from Alteromonas were available, including Siphoviridae phages PB15, JH01, P24, XX1924, and R7M and R9Y-phages ( 25 29 ), Myoviridae phage V22 ( 30 ), Podoviridiae phages altaD45 P1 to P4 ( 31 ) and Mareflavirus phage ZP6 ( 32 ), Autographiviridae phages H4/4’ ( 33 ) and R8W ( 34 ). Different from the above phages, ϕAFP1 consisted of a flexible filament (width = 10 nm, length = 900 nm), suggesting that this phage was a member of the family Inoviridae .…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we reported the isolation and complete genome sequence of a filamentous phage designated ϕAFP1 from the South China Sea using the A. abrolhosensis strain JKT1 as the host bacterium. Until now, only 10 published reports about bacteriophages isolated from Alteromonas were available, including Siphoviridae phages PB15, JH01, P24, XX1924, and R7M and R9Y-phages ( 25 29 ), Myoviridae phage V22 ( 30 ), Podoviridiae phages altaD45 P1 to P4 ( 31 ) and Mareflavirus phage ZP6 ( 32 ), Autographiviridae phages H4/4’ ( 33 ) and R8W ( 34 ). Different from the above phages, ϕAFP1 consisted of a flexible filament (width = 10 nm, length = 900 nm), suggesting that this phage was a member of the family Inoviridae .…”
Section: Discussionmentioning
confidence: 99%
“…[28]) but also acknowledge that virulent phages can have a very small burst size on certain hosts (e.g. [29][30][31]). The parameter ranges for the plasmid conjugation rates and plasmid fitness effects were chosen in line with two meta-analysis on those two respective parameters [1,32].…”
Section: Methodsmentioning
confidence: 99%
“…[28]) but also acknowledges that virulent phages can have a very small burst size on certain hosts (e.g. [29][30][31]).…”
Section: E) Implementationmentioning
confidence: 99%